The factors that determine elderly satisfaction of elderly activity centre in Shanghai, China - Xue, Kang Huan (2014)
The aging is the fastest growing population in the world. The population of the elderly is expected ti increase with the advancement in medical care and changes in lifestyle. The capability in handling the needs of the rising elderly population has become one of the problems. Therefore, the aim of this study is to find the factors that determine elderly satisfaction of elderly activity centre at Jing'an District in Shanghai, China. This study used servey method in obtaining the data. There are 217 elderly chosen as the sample from each elderly centre of XinFuKangLi and QingSongCheng Elderly activity Centre. There were interviewed using questionnaires that consisted of two parts. Part one contains the background of the respondents and part two contains information regarding frequency of visitations, reason for visitations, location, size, activities and facilities that should be provided to attract the elderly visitors. Frequency and cross tabulation with gamma test were used to analyze the data collected from the questionnaires. As a result, the study found that there is no direct relation between elderly visit with four aspects whch is location, size, activity and facility but it influences the elderly visit. The elderly would like the location of Elderly Activity Centre which is near to community with suitable size and more facilities and activities are provided. The results also show that the elderly likes the centre because of having the facilities for board games such like chess and card games.